2009
DOI: 10.1186/1757-7241-17-61
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined treatment with morphine sulphate and low-dose ketamine in a prehospital setting

Abstract: BackgroundPain is a common condition among prehospital patients. The present study is designed to determine whether adding low-dose ketamine as additional analgesia improves the pain/nausea scores and hemodynamic parameters compared to morphine sulphate alone among patients with bone fractures.MethodsProspective, prehospital clinical cohort study. Twenty-seven patients were included with acute pain. Eleven patients received morphine sulphate 0.2 mg/kg (M-group) and 16 patients received morphine sulphate 0.1 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 9 publications
4
43
1
Order By: Relevance
“…However, 1,014 of these studies were excluded (Fig 1). Among the eligible 20 studies, 3 systematic reviews, 9 non-RCTs [1927] and 2 RCTs [28,29] were excluded: a case series and a letter [19,26], three retrospective studies [2325], studies that used treatments other than intravenous infusion [20,21,23], a prospective study in which both ketamine and hydromorphine were simultaneously used without a control group [22], and another study that was a prospective cohort study with multiple biases, such as selection, performance, detection, and reporting bias [27]. None of the above excluded studies were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…However, 1,014 of these studies were excluded (Fig 1). Among the eligible 20 studies, 3 systematic reviews, 9 non-RCTs [1927] and 2 RCTs [28,29] were excluded: a case series and a letter [19,26], three retrospective studies [2325], studies that used treatments other than intravenous infusion [20,21,23], a prospective study in which both ketamine and hydromorphine were simultaneously used without a control group [22], and another study that was a prospective cohort study with multiple biases, such as selection, performance, detection, and reporting bias [27]. None of the above excluded studies were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Several small observational or open-label studies have demonstrated either morphine-sparing effects or reductions in pain severity when low-dose ketamine is employed for pain in the prehospital or ED setting. [8][9][10][11][12] However, lack of randomized controlled clinical trials examining the effectiveness of low-dose ketamine in the ED may partly explain why it has not been incorporated into regular clinical practice. In addition, guidance is needed regarding the optimum dose for ketamine as an adjunct analgesic; studied doses have ranged from 0.05 to 1 mg/kg, and various methods and routes of administration have been employed (single bolus, repeat dosing, or continuous infusion; IV, intramuscular, intranasal, or intrathecal).…”
mentioning
confidence: 99%
“…Galinski et al [16] treated patients experiencing severe pain in mobile intensive care units in a double-blind RCT and found a statistically significant (P = 0.002) increase in neuropsychological adverse effects (36% vs 3%) with administration of 0.2 mg/kg intravenous ketamine compared to morphine including hallucinations, dizziness, diplopia, and dysphoria. Gurnani et al [17] showed less overall nausea, whereas Johansson et al [21] showed more overall nausea in the morphine only group vs the ketamine plus morphine group. In an RCT by Weinbroum [10], intravenous ketamine (0.25 mg/kg, n = 131) plus morphine (0.015 mg/kg) vs morphine alone (0.030 mg/kg, n = 114) resulted in less postoperative nausea and ☆ Explanation of lead authors credentials.We believe Heidi Riha, BS, PharmD Candidate 2015, has the qualifications and contributions to the paper to establish herself as the lead author.…”
Section: To the Editormentioning
confidence: 97%
“…Most of the studies evaluating ketamine as an analgesic in the emergency setting used it as adjunctive therapy in addition to an opioid [7,16,17,[20][21][22][23][24][25][26]. A few observational studies and one randomized controlled trial (RCT) evaluated the use of low-dose ketamine alone [19,[27][28][29].…”
Section: To the Editormentioning
confidence: 98%
See 1 more Smart Citation